Procedimiento de auditoría interna y gestión económica de la Municipalidad Distrital de Ucayali Contamana, año 2022 - Sarabia Saenz, Fiorella Mirella (2022)
The present investigation had as objective to determine the relationship between the internal audit procedure and the economic management of the District Municipality of Ucayali - Contamana year 2022. Which I take for being an applied type study, descriptive level - correlational and non-experimental design. In the investigation, the survey was used as a technique and the questionnaire as an instrument to collect the necessary information. It is concluded that the internal audit procedure is qualified as regular (24%) because sometimes the auditors carry out a good programming of activities for the development of the internal audit, likewise, sometimes it is processed in physical and virtual instruments that allow its better analysis. Also, economic management is considered regular by 26% since it sometimes contains the activities required for the development of the audit; In addition, they almost never carry out the constant analysis and verification of the capacity and distribution of the adequate use of resources; Finally, sometimes the results of the Statement of Financial Position, Statement of Income are analyzed to identify opportunities and risks. Finally, it was determined that there is a relationship between the internal audit procedure and economic management, which has been contrasted by a correlation coefficient of (0.762) this is at a considerable positive level, with bilateral significance of 0.000.